Flammability on textile of business uniforms: use of natural fibers. (2017) - Silva-Santos, Marcia Cristina; Oliveira, Marcelo Silva; Giacomin, Alessandra Maria; Laktim, Mariana Costa; Baruque-Ramos, Julia
Abstract: The flammability issue of textile materials employed in business uniforms becomes an important part in the management of worker safety, as in the case of electricians or kitchen chefs. Among the categories that wear business uniforms, the aeronauts are trained among other activities to fight fire on board. It is part of the crew functions, notably the flight attendants in-flight fire event. This study compares the Limiting Oxygen Index (LOI) values to the key fibers (including that ones from natural origin) used on professional clothing material. The range of LOI index presented of the materials used in the preparation of professional uniforms was from 17.4 to 30%. The variation represents the difference in materials origins and their chemicals structures, relative to flame resistance.